2009
DOI: 10.2215/cjn.03910808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Long-Term Outcome of Nephrotic Syndrome Associated with Heterozygous NPHS1 and NPHS2 Mutations

Abstract: Results: Patients with a single mutation in NPHS1 received a diagnosis before those with potentially nongenetic NS and had a good response to therapies. Renal function was normal in all cases. For NPHS2, six patients had single heterozygous mutations, six had a p.P20L variant, and 21 had a p.R229Q variant. Age at diagnosis and the response to drugs were comparable in all NS subgroups. Overall, they had similar renal survival probabilities as non-NPHS1/NPHS2 cases (log-rank 2 0.84, P ‫؍‬ 0.656) that decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
4
21
0
1
Order By: Relevance
“…Patient 7 was clinically diagnosed with NS at the age of 58 months; she failed to respond to either steroid or cyclosporin A treatment, and her renal pathology showed changes of FSGS. These clinical features were similar to those of patients with homozygous mutations or compound heterozygous mutations, or a heterozygous pathogenic mutation, in their NPHS1 genes, as reported previously (Heeringa et al, 2008;Philippe et al, 2008;Caridi et al, 2009;Santín et al, 2009). It is likely that the compound heterozygous state of the NPHS1 mutations caused development of SRNS in patient 7.…”
Section: Discussionsupporting
confidence: 87%
“…Patient 7 was clinically diagnosed with NS at the age of 58 months; she failed to respond to either steroid or cyclosporin A treatment, and her renal pathology showed changes of FSGS. These clinical features were similar to those of patients with homozygous mutations or compound heterozygous mutations, or a heterozygous pathogenic mutation, in their NPHS1 genes, as reported previously (Heeringa et al, 2008;Philippe et al, 2008;Caridi et al, 2009;Santín et al, 2009). It is likely that the compound heterozygous state of the NPHS1 mutations caused development of SRNS in patient 7.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies did not report any polymorphism in SRNS [18], however, higher percent of this polymorphism was found by many other studies [18]. In addition, The polymorphism R229Q was absent among SSNS and SRNS subcategories a finding which was detected by Landau et al [25] who did not find any polymorphisms in SSNS, as well as Lahdenkari et al, [26] and Caridi et al, [27]. Our results concerning the absence of the NPHS2 R229Q…”
Section: Subjects With Minimal Change Disease (Mcd)supporting
confidence: 50%
“…It is now well established that R229Q is a frequent cause of nephrotic syndrome when found in compound heterozygosity with other NPHS2 mutations [11][12][13]. Additionally, Pereira et al [8] reported that R229Q is responsible for microalbuminuria in the general population.…”
Section: Resultsmentioning
confidence: 99%